2021
DOI: 10.3390/foods10092186
|View full text |Cite
|
Sign up to set email alerts
|

Research Advances of d-allulose: An Overview of Physiological Functions, Enzymatic Biotransformation Technologies, and Production Processes

Abstract: d-allulose has a significant application value as a sugar substitute, not only as a food ingredient and dietary supplement, but also with various physiological functions, such as improving insulin resistance, anti-obesity, and regulating glucolipid metabolism. Over the decades, the physiological functions of d-allulose and the corresponding mechanisms have been studied deeply, and this product has been applied to various foods to enhance food quality and prolong shelf life. In recent years, biotransformation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 142 publications
(168 reference statements)
0
15
0
Order By: Relevance
“…More than 30 kinds of rare sugars have been reported ( Granström et al, 2004 ). They have unique biological functions and have been used as food additives, cancer cell suppressors, and building blocks for anticancer and antiviral drugs ( Zhang et al, 2016b ; Li et al, 2017 ; Guerrero-Wyss et al, 2018 ; Hoshikawa et al, 2018 ; Xia et al, 2021 ). D-Allulose (also called D-psicose) is well known as the most remarkable of rare sugars.…”
Section: Introductionmentioning
confidence: 99%
“…More than 30 kinds of rare sugars have been reported ( Granström et al, 2004 ). They have unique biological functions and have been used as food additives, cancer cell suppressors, and building blocks for anticancer and antiviral drugs ( Zhang et al, 2016b ; Li et al, 2017 ; Guerrero-Wyss et al, 2018 ; Hoshikawa et al, 2018 ; Xia et al, 2021 ). D-Allulose (also called D-psicose) is well known as the most remarkable of rare sugars.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that d -allulose exhibits different water-binding properties compared to other monosaccharides [ 13 ], and physical properties of the confectionery products can be affected by the water binding ability of sugars used in formulations. d -allulose has a wide array of biomedical applications, such as improving insulin resistance, its anti-obesity effects, its anti-inflammatory nature, and in regulating glucolipid metabolism [ 14 , 15 ]. It is also worth mentioning that d -allulose intake improves cholesterol metabolism, leading thus to a reduced risk of atherosclerotic plaque formation, which is considered a major cause of ischemic heart disease [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The excessive intake of high energy sugars has caused many health problems, such as diabetes, hypertension, hyperlipidemia, and other diseases (Xia et al, 2021). D-allulose (D-psicose or D-ribo-2-hexulose) is a good sugar substitute, because it is an low calorie sweeter (70% sweetness of sucrose), and inert in energy metabolism (Iida et al, 2010).…”
Section: Introductionmentioning
confidence: 99%